2017
DOI: 10.1016/j.jjcc.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3-dimensional and 2-dimensional quantitative coronary angiography and intravascular ultrasound for functional assessment of coronary lesions

Abstract: 3D-QCA is more useful than 2D-QCA and possibly comparable to IVUS in the assessment of functional stenosis severity. When FFR is not available, 3D-QCA MLA and MLD may assist in the assessment of functional severity of intermediate lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…It is known that visual-functional mismatches between angiography and FFR are observed in a non-negligible proportion of intermediate stenosis, which is attributed to multiple factors [5]. Although several small-sized studies have demonstrated the capability of coronary angiography for prediction of functionally ischemic lesions, using new technologies such as 3-dimensional quantitative coronary angiography [6] or computational fluid dynamics modeling [7], the capability is not sufficiently corroborated by sufficient evidence. Also, given the different concepts between the blood flow dynamics in the coronary lumen and morphologic characteristics of vessel wall outside the coronary lumen, prediction of FFR by imaging modalities has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that visual-functional mismatches between angiography and FFR are observed in a non-negligible proportion of intermediate stenosis, which is attributed to multiple factors [5]. Although several small-sized studies have demonstrated the capability of coronary angiography for prediction of functionally ischemic lesions, using new technologies such as 3-dimensional quantitative coronary angiography [6] or computational fluid dynamics modeling [7], the capability is not sufficiently corroborated by sufficient evidence. Also, given the different concepts between the blood flow dynamics in the coronary lumen and morphologic characteristics of vessel wall outside the coronary lumen, prediction of FFR by imaging modalities has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, 3D QCA, which was first conceived earlier [36], was applied to clinical practice. In the 2010s, the angiography-derived FFR method based on 3D QCA was introduced for a more accurate assessment of clinically significant stenosis [37]. Tu et al showed that the angiography-derived FFR exhibits good correlation with FFR [38].…”
Section: History and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, it averts inaccurate length measurement due to vessel shortening, which is frequently observed in 2D QCA. It was reported that the 3D QCA parameters more precisely reflected the luminal dimensions measured through intravascular ultrasound and FFR compared with 2D QCA [37,59]. The advantage of 3D QCA is highlighted in the assessment of bifurcation.…”
Section: D Quantitative Coronary Angiographymentioning
confidence: 99%
“…D e d i c a t e d 3 -d i m e n s i o n a l ( 3 D ) a n g i o g r a p h i c reconstruction algorithms were developed to overcome some of the inherited limitations in 2D-QCA analysis such as foreshortening and out-of-plane magnification (5,6). Excellent correlation was reported between 3D-QCA and intravascular imaging including intravascular ultrasound (IVUS) (7) and optical coherence tomography (OCT) (5). Compared with 2D-QCA, 3D-QCA reported better diagnostic performance for predicting physiologically significant coronary stenosis when FFR was used as the reference standard (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Excellent correlation was reported between 3D-QCA and intravascular imaging including intravascular ultrasound (IVUS) (7) and optical coherence tomography (OCT) (5). Compared with 2D-QCA, 3D-QCA reported better diagnostic performance for predicting physiologically significant coronary stenosis when FFR was used as the reference standard (7)(8)(9). Nevertheless, these studies had a relatively small population size and were limited by their retrospective design.…”
Section: Introductionmentioning
confidence: 99%